Learning to Work: Young People's Social and Labour-Market Integration through Supra-Company Apprenticeship Training in Austria - Bettina Haidinger; Ruth Kasper (Social Work & Society, 2012)
The institutionalisation of supra-company apprenticeship training after its incorporation into the Vocational Education and Training Act in 2009 was a political signal to acknowledge a kind of third pillar next to school-based education and company-based apprenticeship training after compulsory schooling within the Austrian educational system. However due to the deep-rooted persistence of the dual system, it is still regarded as a "buffer" when the former fails to provide sufficient placements. As the Supra-Company-Apprenticeship Training is part of active labour market policy students are still clients of the Public Employment Service - and not (just) young persons to be educated. Therefore, one main challenge providers of SCAT have to cope with is to prepare students on the one hand for their placement within the regular apprenticeship system and on the other hand to provide high-quality vocational training as a valuable offer. This janus-faced pedagogical treatment of students has a major impact on the students' development of capabilities for education, for work and for voice in a system with notably transitory character. This contribution will first give a short overview of the case study's institutional embeddedness. After a brief introduction into the research methods used, we will outline the key findings of the case study from a capability perspective: First, the capability approach endorses education from two perspectives: Education is a capability to be achieved as such. Education also serves as a conversion factor for other capabilities. We will present findings for these two notions, including an analysis of the (two) crucial phases for choosing the educational pathway one has reason to value and a discussion of the training's empowerment dimension in terms of 'learning (how) to work'. Second, turning to the capability for work we will on the one hand question the principal notion of work proposed by the capability approach and then lay down the youngsters' perception of 'decent work' in labour processes. Finally, we will take a look at what opportunities for voice and for being able and 'free' to choose, aspire and follow the life, work and educational pathway they have reason to value do youngsters encounter before and while participating in SCAT.